A comparative analysis of technical efficiency and profitability of agribusiness and non-agribusiness enterprises in eastern DRC - Nyamuhirwa, D.A.; Awotide, B.A.; Kusinza, D.B.; Bishikwabo, K.; Mignouna, J.; Bamba, Z.; Dontsop Nguezet, Paul M. (MDPI, 2022)
The purpose of this study was to determine whether agribusiness could be competitive compared to non-agribusiness employment opportunities in terms of technical efficiency and profitability. We used data collected on all seven operating cassava community processing centers (CCPCs) and 150 comparable non-agribusiness enterprises in South Kivu province. A Data Envelopment Analysis (DEA), as well as cost–benefit ratios and net monthly revenue, were used to examine technical efficiency and profitability. Our results showed that agribusiness was more competitive than non-agribusiness in terms of technical efficiency and profitability. The cost–benefit ratio shows that every dollar invested in agribusiness earns investors US $2.8, while it earns investors in non-agribusiness US $2.1. Moreover, technical efficiency increases significantly with agribusiness. These results show that agribusiness can compete with other non-agribusiness activities, and it remains a solution to youth unemployment in the region.